2010
DOI: 10.1200/jco.2009.24.8005
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Spiritual Care to Patients With Advanced Cancer: Associations With Medical Care and Quality of Life Near Death

Abstract: Support of terminally ill patients' spiritual needs by the medical team is associated with greater hospice utilization and, among high religious copers, less aggressive care at EoL. Spiritual care is associated with better patient QoL near death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
310
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(333 citation statements)
references
References 32 publications
11
310
0
12
Order By: Relevance
“…The essence of spiritual care is being rather than simply doing [24]. Thus, therapeutic use of self is of utmost importance [25].…”
Section: Definition Of Spiritual Carementioning
confidence: 99%
“…The essence of spiritual care is being rather than simply doing [24]. Thus, therapeutic use of self is of utmost importance [25].…”
Section: Definition Of Spiritual Carementioning
confidence: 99%
“…Studies on the subject under discussion have shown that spirituality has a strong influence on the HRQoL of people with advanced disease and the evaluation of its dimensions cannot be measured without considering the dimension of spirituality, at the risk of not having a proper assessment (22,24) . Thus, these studies may lead to reflections on the role of caregivers as enablers of the inclusion of spiritual need in the context of a holistic patient and family care.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies evaluated the HRQoL of patients by performing therapeutic interventions, distributed as follows: six were on physical interventions (12)(13)(14)(15)(16)(17) , four were on emotional interventions (18)(19)(20)(21) , and three were on spiritual interventions (22)(23)(24) (Chart 1). Finally, eight studies addressed the signs and the symptoms that negatively affected the HRQoL of patients with advanced cancer (25)(26)(27)(28)(29)(30)(31)(32) (Chart 2).…”
Section: Characterization Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Spirituality is an important component of quality of life, and a resource in patients coping with illness. [3][4] In elderly populations, spirituality is probably a signi cant factor when facing disability and approaching death. [5][6][7] While spirituality was associated with better mental, physical and social health in most researches, [8][9] other studies have also suggested that some negative aspects of spirituality (e.g., "low spiritual well-being" or "religious struggle"), might be associated with worse health outcomes.…”
Section: Introductionmentioning
confidence: 99%